Informatics in Schools. New Ideas in School Informatics 12th International Conference on Informatics in Schools: Situation, Evolution, and Perspectives, ISSEP 2019, Larnaca, Cyprus, November 18–20, 2019, Proceedings - Pozdniakov, Sergei N.; Dagienė, Valentina (Theoretical Computer Science and General Issues, 2019)
XI, 305 p. 86 illus., 53 illus. in color.